CLEANER PRODUCTION FOR SOLID WASTE MANAGEMENT IN LEATHER INDUSTRY - Woldeyes, Belay (Zede Journal of Ethiopian Engineers and Architects, 2023)
The leather industry is characterized as an industry that uses many chemicals and large quantity of water. From the processes, wastes aYe generated which include wastewater effluents, solid wastes, and hazardous wastes. In developing countries including Ethiopia, many leather industries discharge wastes into the environment without any proper treatment. The best approach to reduce the environment burden is to eliminate the problem at source, using cleaner production options. In this paper, the study is peiformed in one of the leather industry in Ethiopia, namely Addis Ababa Tannery by · implementing cleaner production methodologies. The solid waste inventory of the factory has b en carried out. The major problems have been identified. Jn order to accomplish this, the possible cleaner production steps have been suggested. Technical and economical aspects of the best steps have been evaluated. Result of the study indicates that the implementation of the suggested cleaner production steps would bring about significant benefits for the factory.